Seeking Skillful Means: Approaches to Political Polarization Among Finnish Extinction Rebellion Activists Practicing Buddhism - Cairns, Johannes ca. 20./21. Jh. (Nordic journal of religion and society, 2025)
Socially engaged Buddhists experience tensions around reconciling equanimity and nonattachment with assertive activism. These tensions risk being be exacerbated by political polarization, which emphasizes opposition and confrontation between groups of people. However, there is a dearth of empirical studies exploring this theme. This study explores how Western Buddhists negotiate climate activism amid political polarization, focusing on 12 Finnish Buddhist practitioners involved in Extinction Rebellion Finland's 2024 protests. Surprisingly, most participants interpreted compassion as a justification for disruptive protest, even if it heightened polarization. They combined compassion with secular interpretations on protest strategies with the highest efficacy, applying the Buddhist concept of skillful means to navigate these challenges. Many also expressed compassion toward political opponents. The findings suggest that Buddhist teachings can mediate the impact of activism on political polarization by shaping group identity and protest strategies, highlighting how religion-specific concepts influence political engagement.